Evaluation of tropical seaweeds as feedstock for bioethanol production - Hessami, Mohammad Javad; Phang, Siew Moi; Salleh, Aishah; Rabiei, Reza (Springer Verlag, 2018)
Limited resources of freshwater and decreasing fossil fuel resources are two main reasons to consider the ocean as a huge resource for producing food, feed, fertilizer and feedstock for fuel. In this study, twenty-nine tropical seaweeds (11 green, 10 red and 8 brown seaweeds) collected in Malaysia were assessed as potential feedstock for bioethanol production. Total carbohydrate content ranged from 12.16 to 71.22% dry weight (DW) with total reducing sugar content ranging from 5.17 to 34.12% DW. During hydrolysis using dilute sulphuric acid, the dominant fermentation inhibitors were 5-hydroxymethylfurfural and phenolic compounds. Overliming was found to reduce the content of fermentation inhibitors by up to 79%. The red seaweeds, Kappaphycus alvarezii (Doty) Doty ex P.C.Silva and Gracilaria manilaensis Yamamoto and Trono, were selected for optimization of saccharification and fermentation of the hydrolysate, because they had the highest carbohydrate contents and are commercially cultivated. The most suitable dilute acid conditions obtained in present study was sulphuric acid (2.5%, w v−1) treatment at 121 °C for 40 min that produced 0.29 and 0.34 g g−1 DW reducing sugar for K. alvarezii and G. manilaensis, respectively. Fermentation of the hydrolysates with Saccharomyces cerevisiae produced bioethanol yields of 20.90 g L−1 (71.0% of theoretical yield) for K. alvarezii and 18.16 g L−1 (67.9% theoretical yield) for G. manilaensis.